INKLUSIFISME DAN EKSKLUSIFISME SERTA PENGARUHNYA TERHADAP PENDIDIKAN MULTIKULTURAL - Muhammad Asrori; M. Muizzuddin; Kusnan Kusnan; Moh. Solihuddin (JP : JURNAL PENDIDIKAN, 2019)
Abstract: This article is organized in connection with the increasingly widespread attitude of intolerance in society. Especially intolerance in the name of religion. In this case the writer will reveal earlier about inclusive attitudes that is placing the perspective of other people/ other groups in seeing the world, in other words trying to use the perspective of others or other groups in understanding the problem. Contrary to that, an exclusive attitude. Some things that lay behind the exclusive nature, including the lack of meaning of religious values and excessive fanaticism. Multicultural education is an alternative solution to the inclusive attitude. Multicultural education is an effort and process of empowering diverse and heterogeneous societies to understand and respect one another and form characters that are open to differences. This is also in line with the practice of surah Al-Hujurat verse 13.Keywords: Inclusiveism, Exclusiveism, Multicultural Education